LEGAL AND SOCIAL COMPLEXITIES RELATING TO PRACTICE OF ARRANGED AND FORCED MARRIAGES - Booley, Ashraf (Jurnal Syariah, 2021)
The practice of forced and/or arranged marriages are reported to be taking place globally. These types of marriages have become gender neutral and can no longer be described only as an issue relating to women. However, what is portrayed is that women normally suffer as reported cases are evidence of that. First world countries where there is a large immigrant community, frown on the practice of forced marriages and arranged marriages. This is a complex issue, because on the one hand, one’s religious, cultural diversity is attacked and on the other hand forced and arranged marriages may violate various provisions of international, regional national human rights instruments. From an international law perspective, one could argue that there is a clear violation of international law. On the other hand, and argument relating to one’s cultural and religious beliefs could also be advanced. Concepts such as culture, religion and gender are deeply embedded in most known religions and communities, therefore, the practice of forced and arranged marriages may not be perceived as violation of any law/s whether international or national. Furthermore, forced and arranged marriages are at times so interrelated that it may be difficult to draw a clear distinction between the two. How do we protect women’s rights while at the same time respecting the cultural diversity of society? This article attempts to add to the existing debate surrounding the social and legal complexities of forced and arranged marriages.